Designing for Engagement: The Influence of LMS Features on Online Formative Assessment in Tanzania Higher Learning Institutions - Shafraeli, Evaline; Ngeze, Lucian; Gilbert, Gilbert Mapunda (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
This study examined student engagement in Online Formative Assessment (OFA) across six higher education institutions in Tanzania, and how LMS design features—specifically assignment clarity, feedback quality, usability, and mobile accessibility—relate to student perceptions and engagement levels. A quantitative cross-sectional design was employed, involving 214 students from six (6) higher institutions in Tanzania. Data were collected using structured questionnaires and analyzed through descriptive statistics and multiple regression techniques. Overall engagement with OFA tools was high, with students reporting strong agreement on the importance of clear assignment guidelines (82.7%), timely feedback (81.7%), and intuitive LMS interfaces (79.2%). Regression analysis revealed significant positive associations for feedback quality (β = 0.41, p < .001), LMS usability (β = 0.38, p < .001), and assignment clarity (β = 0.35, p < .001). Mobile accessibility showed a moderate but meaningful effect (β = 0.24, p = .002), highlighting its emerging role in inclusive digital learning. The adjusted R² value of 0.42 indicated that 42% of the variance in student engagement was explained by the combined predictors. Participants cited challenges such as inconsistent mobile optimization, limited digital literacy, and delayed feedback. The study recommends standardizing LMS design templates, investing in mobile-first development, and strengthening instructor training to improve OFA effectiveness. It also calls for further research on mobile learning strategies and longitudinal impacts of LMS design improvements in bandwidth-constrained environments.